High Refractive Index Sensor for Tellurite Photonic Crystal Fiber Based on Soliton Self-Frequency Shift - Di Wu; Jing Zhang (IEEE Photonics Journal, 2024)
In this paper, a novel refractive index (RI) sensor based on the soliton self-frequency shift (SSFS) in tellurite photonic crystal fiber (TPCF) is proposed. RI sensing in the mid-infrared region is achieved by detecting the wavelength shift of the soliton. By exploiting the high RI property of the tellurite fiber, it is possible to measure surrogate liquids with higher RIs compared to conventional silica fibers. The sensitivity of the proposed sensor can reach up to 3657.5 nm/RIU when a fiber laser with a pulse width of 100 fs and pump wavelength (λP) of 2600 nm is used as the light source and a 1 m-long TPCF is utilized as the nonlinear medium. To the best of our knowledge, this is the first time that high RI sensing in the mid infrared region has been achieved by exploiting the SSFS effect in non-silica fibers such as TPCF.